Psoriasis and risk of central neurological disorders in European populations: A mendelian randomization analysis - Ya Li; Jun Cai; Huimin Chong (Heliyon, 2024)
Background: People with psoriasis are at a higher risk for having central neurological problems, according to previous studies; however, it is unclear if there is a genetic link between the risk of developing psoriasis and developing central neurological disorders. In this study, the possible link between genetically predisposed psoriasis and the risk of common central nervous system disorders was comprehensively investigated. Methods: There was no overlap in the participant populations between the psoriasis and central neurological disorders genome-wide association studies, which provide the genetic resources. Inverse variance weighting, often used as Mendelian randomization (MR) analysis, is the main method. To guarantee the accuracy of our findings, a number of sensitivity studies were carried out. Results: MR analysis revealed that although psoriasis was reported to increase the risk of Parkinson's disease (OR = 4.42, 95%CI[-3.81～6.79], P = 0.58) and epilepsy (OR = 4.71, 95%CI[-2.20～5.30], P = 0.42) in this study, they did not reach statistical significance. At the same time, this study did not observe that psoriasis would increase the risk of multiple sclerosis (OR = 0.01, 95%CI [-12.61～3.83], P = 0.30) and migraine (OR = 0.99, 95%CI [0.94～1.05], P = 0.78), they also did not reach statistical significance. Under all sensitivity assessments, the results remained stable. Conclusions: Psoriasis does not appear to raise the risk of migraine, Parkinson's disease, multiple sclerosis, or epilepsy, according to our study.